Correlation of HbA1c with Ratio of Total Cholesterol/HDL, LDL/HDL, TG/HDL and Apolipoprotein B / Apolipoprotein A-1 Ratio in Patients with Type 2 Diabetes Mellitus - Irmawati,; Kurniawan, Liong Boy; Bahrun, Uleng; Sanusi, Himawan; Kadir, Nursin Abdul; Bahar, Burhanuddin (Gaceta Médica de Caracas, 2023)
Background: The lipid and Apo B/Apo A-1 ratios may be considered additional risk factor assessments, especially in patients with a high risk of cardiovascular diseases, such as diabetes. Blood glucose level can be assessed by measuring glycated hemoglobin (HbA1c), which is used as a long-term control and monitoring. Objective: This study aimed to determine the relationship between HbA1c with lipid ratio and Apolipoprotein B/Apolipoprotein A-1 ratio in patients with type 2 diabetes mellitus.